CERTAIN ISSUES OF ADMINISTRATIVE RESPOSIBILITY OF THE CREW OF THE AIRCRAFT OF UKRAINE - Дараганова, Н. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with issues of legal regulation of disciplinary liability of aviation personnel of civil aviation of Ukraine.